Battery cell, method for producing the same, battery device, electric device, and energy storage device

CN122931179APending Publication Date: 2026-10-16JINKO SOLAR CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611327853.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

本申请利用电池单体外壳和顶盖不同材料的不同热膨胀系数,实现了动态自紧(区别于传统的纯机械紧固);同时,外壳和顶盖之间采用玻璃态材料原位密封,耐腐蚀性提升,因此,实现了在1.5MPa内压测试下保持24h无泄漏,1000次热循环(-20℃~80℃)后,界面接触电阻增加<5%,浸泡在NaPF6电解液中6个月后,密封层厚度不减少。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931179A_ABST
    Figure CN122931179A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of energy storage, and provides a battery monomer, a preparation method of the battery monomer, a battery device, a power utilization device and an energy storage device. The battery monomer comprises: an electrode core assembly, the electrode core assembly comprises a negative electrode sheet, a diaphragm and a positive electrode sheet which are arranged in a stack; a shell, the electrode core assembly is located in the shell; and an electrolyte, the electrolyte is located in the shell. The shell comprises an outer shell and a top cover, the material of the outer shell has a first thermal expansion coefficient, the material of the top cover has a second thermal expansion coefficient, the first thermal expansion coefficient is different from the second thermal expansion coefficient, and the outer shell and the top cover are both provided with sealing layers. The application is at least beneficial to improving the sealing performance of the battery monomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of energy storage technology, and in particular to a battery cell and its preparation method, a battery device, an electrical device, and an energy storage device. Background Technology

[0002] When a battery cell is in use, the quality of its sealing performance has a significant impact on its overall performance. Therefore, high requirements are placed on the sealing structure of the battery cell. The sealing structure is not a single component, but a sophisticated system designed to ensure the safety, stability, and long lifespan of the battery. Its core mission is to completely isolate the sensitive electrochemical system inside the battery from the external environment. Among these components, the seal between the outer casing and the top cover is the most fundamental structural seal of the battery, determining its overall airtightness and mechanical strength. Summary of the Invention

[0003] This application provides a battery cell and its preparation method, a battery device, an electrical device, and an energy storage device, which at least helps to improve the sealing performance of the battery cell.

[0004] In a first aspect, this application provides a battery cell, comprising: A battery cell assembly, the battery cell assembly comprising a negative electrode, a separator and a positive electrode stacked together; The housing, in which the battery cell assembly is located; Electrolyte, wherein the electrolyte is located within the housing; The housing includes an outer shell and a top cover. The material of the outer shell has a first coefficient of thermal expansion, and the material of the top cover has a second coefficient of thermal expansion. The first coefficient of thermal expansion is different from the second coefficient of thermal expansion. A sealing layer is provided between the outer shell and the top cover.

[0005] Optionally, the absolute value of the difference between the first coefficient of thermal expansion and the second coefficient of thermal expansion is not less than 10 × 10⁻⁶. -6 / K.

[0006] Optionally, the material of the outer casing includes at least one of aluminum alloy and magnesium alloy, and the material of the top cover includes at least one of titanium alloy and stainless steel; or, the material of the outer casing includes at least one of titanium alloy and stainless steel, and the material of the top cover includes at least one of aluminum alloy and magnesium alloy.

[0007] Optionally, the outer casing has an opening, the edge of the top cover has a first flange, and the inner side of the opening has a first groove that mates with the first flange; or, the edge of the top cover has a second groove, and the inner side of the opening has a second flange that mates with the second groove.

[0008] Optionally, the edge of the top cover has a first flange, and the inner side of the opening has a first groove that mates with the first flange; there is a gap between the first flange and the first groove.

[0009] Optionally, both the first flange and the second flange have a first surface and a second surface, with an angle α between the first surface and the second surface. The inner side of both the first groove and the inner side of the second groove have a third surface and a fourth surface, with an angle β between the third surface and the fourth surface, where 20°≤β-α≤30°.

[0010] Optionally, 20°≤α≤40°; and / or, 50°≤β≤70°.

[0011] Secondly, this application provides a method for preparing a battery cell as described above, comprising: A battery cell assembly and an electrolyte are obtained, wherein the battery cell assembly includes a negative electrode, a separator, and a positive electrode stacked together; Obtain the outer casing and top cover, install the battery cell assembly into the outer casing, and assemble the top cover and the outer casing into a housing; The electrolyte is injected into the housing; Perform the formation step; The housing includes an outer shell and a top cover. The material of the outer shell has a first coefficient of thermal expansion, and the material of the top cover has a second coefficient of thermal expansion. The first coefficient of thermal expansion is different from the second coefficient of thermal expansion. A sealing layer is provided between the outer shell and the top cover.

[0012] Optionally, the assembly steps include: Sealant is applied to the contact surfaces of the outer casing and the top cover; After assembly at the first temperature and first pressure, the pressure is released at a rate not exceeding 0.5 MPa / s; Vacuum drying was performed at a second temperature and a second pressure. The first temperature is lower than the second temperature, and the first pressure is greater than the second pressure.

[0013] Optionally, the sealant is applied by slit extrusion, with a linear velocity controlled at 0.5 m / s to 1.2 m / s.

[0014] Optionally, the first temperature is 10℃~20℃, and the second temperature is 40℃~50℃.

[0015] Optionally, the first pressure is 15MPa~25MPa, and the second pressure does not exceed 10Pa.

[0016] Optionally, the sealant includes at least one of the following: a gel containing sodium silicate, a gel containing potassium silicate, a sol containing nano-silica particles, and a phosphate adhesive.

[0017] Optionally, the thickness of the sealing layer is 8μm to 12μm.

[0018] Thirdly, this application provides a battery device, including the battery cell as described above, or the battery cell obtained by the preparation method described above, wherein the battery device includes one or more of the following: battery module, battery pack, and energy storage battery.

[0019] Fourthly, this application provides an electrical device, which includes a battery device as described above, the battery device being used to provide electrical energy.

[0020] Electrical devices include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Among them, electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.

[0021] Fifthly, this application provides an energy storage device, which includes a battery device as described above, the battery device being used to store electrical energy.

[0022] Energy storage devices include, but are not limited to, residential energy storage cabinets, commercial energy storage cabinets, energy storage containers, energy storage racks, energy storage power stations, energy storage battery packs, or portable energy storage systems. Energy storage devices may also include energy management systems (EMS), battery management systems (BMS), and power conversion systems (PCS).

[0023] The technical solution provided in this application has at least the following advantages: This application utilizes the different thermal expansion coefficients of the battery cell casing and top cover made of different materials to achieve dynamic self-tightening (different from traditional purely mechanical fastening); at the same time, the casing and top cover are sealed in situ with glassy material, which improves corrosion resistance. Therefore, it can maintain no leakage for 24 hours under an internal pressure test of 1.5MPa, and after 1000 thermal cycles (-20℃~80℃), the interface contact resistance increases by less than 5%. After being immersed in NaPF6 electrolyte for 6 months, the thickness of the sealing layer does not decrease.

[0024] The battery cells provided in this application can be widely used in battery fields requiring high energy density and long cycle life, including high-end electric vehicle battery systems, portable electronic devices, and large-scale energy storage power stations. The battery cells provided in this application can achieve large-capacity energy storage, comprehensively improving energy density, cycle life, and safety performance. They can meet the needs of long-term energy storage, achieving 4 hours or more of long-term energy storage, for example, in energy storage scenarios of 5 hours, 6 hours, and 8 hours. Long-term energy storage refers to the ability to continuously discharge at rated power for 4 hours or even longer, or to achieve large-scale, low-cost energy storage for several days or months. Attached Figure Description

[0025] One or more embodiments are illustrated by way of example with corresponding pictures in the accompanying drawings. These illustrations do not constitute a limitation on the embodiments. Unless otherwise stated, the pictures in the accompanying drawings do not constitute a limitation on scale. In order to more clearly illustrate the technical solutions in the embodiments of this application or in the conventional technology, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 This is a schematic diagram of the structure of the battery device provided in the embodiments of this application; Figure 2 for Figure 1 A schematic diagram of the decomposition process; Figure 3 This is a structural schematic diagram of one sealing method for the housing in this application; Figure 4 for Figure 3 A magnified view of part A in the middle; Figure 5 This is a schematic diagram of another sealing method for the housing in this application; Figure 6 for Figure 5 A magnified view of part A in the middle.

[0027] Figure 7 The flowchart corresponds to the method for preparing a single battery cell provided in the embodiments of this application.

[0028] In the diagram: 100, battery cell; 10, casing; 20, cell assembly; 11, top cover; 12, outer shell; 3, first flange; 4, first groove; 5, second flange; 6, second groove; 71, first surface; 72, second surface; 81, third surface; 82, fourth surface. Detailed Implementation

[0029] As can be seen from the background technology, the existing battery sealing structures have the following problems: 1. Traditional laser welding seal: The heat-affected zone is prone to shell deformation, and microcracks may occur due to metal fatigue after long-term use; 2. Rubber sealing ring solution: Sodium-ion battery electrolyte (such as NaPF6 / EC-DMC) is prone to corroding rubber, leading to swelling and failure; or lithium-ion battery electrolyte (such as LiPF6 / EC-DMC) will also corrode rubber, leading to swelling and deformation of the sealing ring, and ultimately sealing failure; 3. Bolt fastening structure: Large volume and heavy weight, not suitable for the needs of high energy density batteries.

[0030] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined. Similarly, "multiple sets" refers to two or more sets (including two sets), and "multiple pieces" refers to two or more pieces (including two pieces).

[0031] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0032] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent three cases: A exists, A and B exist simultaneously, and B exists. In addition, the character " / " in this document generally indicates that the related objects before and after it have an "or" relationship.

[0033] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential," etc., indicating orientation or positional relationships, are based on the orientation or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application. For example, if the device or element in the illustration is inverted, then the element described as "below," "under," "below," or "bottom" of other elements or features will be oriented "above" or "top" of said other elements or features. Therefore, the term "below" may cover both above and below orientation depending on the context in which the term is used, which will be obvious to those skilled in the art. Materials may be oriented in other ways (e.g., rotated 90°, inverted, flipped), and the spatial relative descriptive terms used herein may be interpreted accordingly.

[0034] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.

[0035] In the description of embodiments of this application, the terms "about," "approximately," "roughly," or "about" for a numerical value referring to a specific parameter include the numerical value, and those skilled in the art will understand that the deviation from the numerical value is within the acceptable tolerance of the specific parameter. For example, "about" or "about" for a numerical value may include additional numerical values ​​that are in the range of 90.0% to 110.0% of the numerical value, such as in the range of 95.0% to 105.0%, 97.5% to 102.5%, 99.0% to 101.0%, 99.5% to 100.5%, or 99.9% to 100.1%.

[0036] In the accompanying drawings corresponding to the embodiments of this application, the thickness and / or area of ​​layers, films, panels, regions, etc., are enlarged for better understanding and ease of description. Throughout the specification, the same reference numerals denote the same elements. Furthermore, when describing a component as being "generally" formed on another component, it means that the component is not formed on the entire surface (or front surface) of the other component, nor is it formed on a portion of the edge of the entire surface.

[0037] In the description of embodiments of this application, when a component "includes" another component, other components are not excluded unless otherwise stated, and may be further included. When describing a component (such as a layer, film, region, or substrate) on or on the surface of another component, the component may be "directly" located on the surface of the other component, or there may be an intermediate component between the two components. Conversely, when describing a component on the surface of another component, or a component "directly" on another component, or a component surface on which another component is formed or disposed, it indicates that there is no intermediate component between the two components. For simplicity and clarity, various components may be drawn at any scale. In the drawings, some components may be omitted for simplicity.

[0038] The terminology used in the description of the various embodiments herein is for the purpose of describing particular embodiments only and is not intended to be limiting. As used in the description of the various embodiments and the appended claims, the term "the component" is also intended to include the plural form unless the context clearly indicates otherwise.

[0039] The “components” mentioned above can refer to layers, membranes, regions, parts, plates, or structures, etc.

[0040] The embodiments of this application will now be described in detail with reference to the accompanying drawings. However, those skilled in the art will understand that many technical details have been provided in the embodiments of this application to facilitate a better understanding of the application. However, the technical solutions claimed in this application can be implemented even without these technical details and various variations and modifications based on the following embodiments.

[0041] Firstly, this application provides a battery cell 100, such as Figure 1 and Figure 2 As shown, it includes: Battery cell assembly 20, which includes a negative electrode, a separator and a positive electrode stacked together; Housing 10, the battery cell assembly is located inside the housing; Electrolyte, wherein the electrolyte is located within the housing; The housing 10 includes an outer shell 12 and a top cover 11. The material of the outer shell 12 has a first coefficient of thermal expansion, and the material of the top cover 11 has a second coefficient of thermal expansion. The first coefficient of expansion is different from the second coefficient of expansion. A sealing layer is provided between the outer shell and the top cover.

[0042] This application utilizes the different thermal expansion coefficients of the battery cell casing and top cover made of different materials to achieve dynamic self-tightening (different from traditional purely mechanical fastening); at the same time, the casing and top cover are sealed in situ with glassy material, which improves corrosion resistance. Therefore, it can maintain no leakage for 24 hours under an internal pressure test of 1.5MPa, and after 1000 thermal cycles (-20℃~80℃), the interface contact resistance increases by less than 5%. After being immersed in NaPF6 electrolyte for 6 months, the thickness of the sealing layer does not decrease.

[0043] Specifically, the battery cell 100 includes a housing 10 and a cell assembly 20, with the cell assembly 20 housed within the housing 10. The housing 10 provides space for the cell assembly 20, and the housing 10 can have various structures.

[0044] In some embodiments, the housing 10 may include a top cover 11 and a shell 12, the top cover 11 and the shell 12 covering each other, the top cover 11 and the shell 12 together defining a receiving space for accommodating the battery cell assembly 20. The shell 12 may be a hollow structure with one end open, and the top cover 11 may be a plate-like structure, the top cover 11 covering the open side of the shell 12 so that the top cover 11 and the shell 12 together define the receiving space; the top cover 11 and the shell 12 may also be hollow structures with one side open, the open side of the top cover 11 covering the open side of the shell 12. Of course, the housing 10 formed by the top cover 11 and the shell 12 may be of various shapes, such as a cylinder, a cuboid, etc.

[0045] In the battery cell 100, the cell assembly 20 can be a single cell, or there can be two or more cell assemblies 20, with multiple cell assemblies 20 being isolated from each other by an insulating film.

[0046] Optionally, the absolute value of the difference between the first coefficient of thermal expansion and the second coefficient of thermal expansion is not less than 10 × 10⁻⁶. -6 / K.

[0047] Optionally, the material of the outer casing includes at least one of aluminum alloy and magnesium alloy, and the material of the top cover includes at least one of titanium alloy and stainless steel; or, the material of the outer casing includes at least one of titanium alloy and stainless steel, and the material of the top cover includes at least one of aluminum alloy and magnesium alloy.

[0048] Optional, such as Figures 3-6As shown, the outer casing 12 has an opening, the edge of the top cover 11 has a first flange 3, and the inner side of the opening has a first groove 4 that mates with the first flange 3; or, the edge of the top cover 11 has a second groove 6, and the inner side of the opening of the outer casing has a second flange 5 that mates with the second groove.

[0049] Optionally, the edge of the top cover has a first flange, and the inner side of the opening has a first groove that mates with the first flange; there is a gap between the first flange and the first groove.

[0050] Optionally, the first flange 3 and the second flange 5 each have a first surface 71 and a second surface 72, with an included angle α between the first surface 71 and the second surface 72. The inner side of the first groove 4 and the inner side of the second groove 6 each have a third surface 81 and a fourth surface 82, with an included angle β between the third surface 81 and the fourth surface 82, where 20°≤β-α≤30°.

[0051] β-α should be controlled within the range of 20° to 30° to ensure feasible low-temperature assembly, effective high-temperature self-locking, and to avoid stress concentration or interface slippage. If β-α is less than 20°, the interference fit is insufficient, and the high-temperature self-locking effect is weakened. If β-α is greater than 30°, the sharp corner effect is significant, which can easily cut into the material surface and damage the glass sealing layer.

[0052] Optionally, 20°≤α≤40°; and / or, 50°≤β≤70°.

[0053] When α is less than 20° (sharper), the axial pressing force will increase, which can easily damage the gel layer. Furthermore, when self-tightening at high temperatures, an excessive radial component may cause local plastic deformation of the shell. When α is greater than 40° (gentler), the radial self-locking force will be weakened, and the dynamic sealing enhancement cannot be effectively achieved by utilizing the thermal expansion difference. When β is less than 50°, the interference fit is large, which can easily scratch the interface during cold pressing assembly, and may not be able to be fully pressed in at low temperatures. When β is greater than 70°, the interference fit is still sufficient, but an excessive angle will make the contact surface shallower and reduce the sealing path length.

[0054] Optionally, α=30°, β=55°. Tests have shown that the 30° / 55° combination, under an initial pressure of 20MPa, has a maximum interface contact pressure deviation of <±5%, and the sealing performance does not degrade after 1000 thermal cycles.

[0055] Optionally, after the top cover and the outer shell are assembled into a housing, a gap exists between the top cover and the outer shell. The existence of this gap allows the in-situ sealing layer to function. By filling this gap with sealant, all voids formed by angle differences and micro-roughness are completely filled. During battery use, this gel reacts with the material of the outer shell to form a dense, continuous sealing layer.

[0056] Optionally, the thickness of the sealing layer is 8μm to 12μm.

[0057] Optionally, the positive electrode, negative electrode, separator, and electrolyte can all be made of conventional materials in the art. For example, the positive electrode material can be a nickel-cobalt-manganese ternary material, lithium nickel-cobalt-aluminum oxide material, or lithium iron phosphate material; the negative electrode material can be graphite, silicon-based material, or tin-based material; the separator can be a polyolefin separator or a ceramic-coated separator; and the electrolyte can be a system in which lithium salt is dissolved in an organic carbonate solvent. Those skilled in the art can make selections according to actual performance requirements, and this application does not impose any special limitations on this.

[0058] Secondly, this application provides a method for preparing a battery cell as described above, such as... Figure 7 As shown, it includes: S1. Obtain a battery cell assembly and an electrolyte, wherein the battery cell assembly includes a negative electrode, a separator, and a positive electrode stacked together; S2. Obtain the outer casing and top cover, install the battery cell assembly into the outer casing, and assemble the top cover and the outer casing into a housing; S3. Inject the electrolyte into the casing; S4. Perform the formation step; The housing includes an outer shell and a top cover. The material of the outer shell has a first coefficient of thermal expansion, and the material of the top cover has a second coefficient of thermal expansion. The first coefficient of thermal expansion is different from the second coefficient of thermal expansion. A sealing layer is provided between the outer shell and the top cover.

[0059] Optionally, the assembly steps include: Sealant is applied to the contact surfaces of the outer casing and the top cover; After assembly at the first temperature and first pressure, the pressure is released at a rate not exceeding 0.5 MPa / s; Vacuum drying was performed at a second temperature and a second pressure. The first temperature is lower than the second temperature, and the first pressure is greater than the second pressure.

[0060] Optionally, the sealant is applied by slit extrusion, with a linear velocity controlled at 0.5 m / s to 1.2 m / s.

[0061] Optionally, the first temperature is 10℃~20℃, and the second temperature is 40℃~50℃.

[0062] Optionally, the first pressure is 15MPa~25MPa, and the second pressure does not exceed 10Pa.

[0063] Optionally, the sealant includes at least one of the following: a gel containing sodium silicate, a gel containing potassium silicate, a sol containing nano-silica particles, and a phosphate adhesive.

[0064] Thirdly, this application provides a battery device, including the battery cell as described above, or the battery cell obtained by the preparation method described above, wherein the battery device includes one or more of the following: battery module, battery pack, and energy storage battery.

[0065] Fourthly, this application provides an electrical device, which includes a battery device as described above, the battery device being used to provide electrical energy.

[0066] Fifthly, this application provides an energy storage device, which includes a battery device as described above, the battery device being used to store electrical energy.

[0067] To verify the impact of the bimetallic self-locking scheme proposed in this application on the sealing performance of battery cells, this application has designed a series of embodiments and comparative examples.

[0068] Example 1 This embodiment provides a method for preparing a single battery cell, including the following steps: Obtain a battery cell assembly and an electrolyte, the battery cell assembly including a negative electrode, a separator and a positive electrode stacked together; Obtain the outer casing and top cover, install the battery cell assembly into the outer casing, and assemble the top cover and the outer casing into a housing; The electrolyte is injected into the housing; Perform the formation step; The outer shell is made of aluminum alloy AA3003, with a coefficient of thermal expansion of 23.6 × 10⁻⁶. -6 / K, the top cover is made of titanium alloy Ti-3Al-2.5V, with a coefficient of thermal expansion of 8.6×10. -6 / K, both the outer shell and the top cover have a sealing layer. The edge of the top cover has a first flange. The first flange has a first surface and a second surface. The included angle between the first surface and the second surface is α, where α is 30°. The outer shell has an opening. The inner side of the opening has a first groove that mates with the first flange. The inner side of the first groove has a third surface and a fourth surface. The included angle between the third surface and the fourth surface is β, where β is 55°. The assembly steps for the housing specifically include: A sodium silicate-containing gel was coated on the contact surface between the outer shell and the top cover using a slit extrusion method at a linear velocity of 0.8 m / s. After assembly at a temperature of (15±2)℃ and a pressure of 20MPa, the pressure is released at a rate not exceeding 0.4MPa / s. Vacuum drying is carried out at a temperature of 45℃ and a pressure not exceeding 10Pa.

[0069] Methods for preparing sodium silicate-containing gels include: Sodium silicate was added to a mixed solvent prepared by adding deionized water and ethanol in a volume ratio of 3:1, and then boric acid, a glass-forming aid, was added. Based on the total mass of the gel, the mass fraction of sodium silicate was 18% and the mass fraction of boric acid was 0.3%.

[0070] The steps involved in the transformation include: (1) Place the assembled battery in a constant temperature environment of 45℃±2℃ and let it stand for 20h~24h for high temperature aging so that the electrolyte can be fully soaked.

[0071] (2) At 45°C, apply a surface pressure of 0.2MPa to 0.5MPa to the battery and charge it with a constant current of 0.02C to 0.05C until it reaches 6%SOC to 15%SOC to complete the formation of the SEI film. Charging with a small current helps to form a dense and stable SEI film.

[0072] (3) After standing for 10 minutes, continue charging with a constant current of 0.1C~0.2C until 30%SOC~40%SOC.

[0073] (4) Charge the device with a constant current and constant voltage at a current of 0.1C~0.5C until the cutoff voltage is 3.65V~3.8V and the cutoff current is 0.02C~0.05C.

[0074] (5) After the formation is completed, the mixture is left to stand under negative pressure at 45°C for 2 to 5 hours. The negative pressure is set to -20 kPa to -30 kPa to remove the gas generated during the formation process and further promote the formation of the SEI film.

[0075] Example 2 This embodiment provides a method for preparing a single battery cell, which differs from Embodiment 1 in that... The housing consists of an outer shell and a top cover. The outer shell is made of aluminum alloy AA3004, with a coefficient of thermal expansion of 23 × 10⁻⁶. -6 / K, the top cover is made of stainless steel with a coefficient of thermal expansion of 14×10. -6 / K, α is 25°, β is 55°.

[0076] During the assembly process: A potassium silicate-containing gel was coated on the contact surface between the outer shell and the top cover using a slit extrusion method at a linear velocity of 0.8 m / s. After assembly at a temperature of (15±2)℃ and a pressure of 20MPa, the pressure is released at a rate not exceeding 0.4MPa / s. Vacuum drying is carried out at a temperature of 45℃ and a pressure not exceeding 10Pa.

[0077] Example 3 This embodiment provides a method for preparing a single battery cell, which differs from Embodiment 1 in that... The casing includes an outer shell and a top cover. The outer shell is made of magnesium alloy with a coefficient of thermal expansion of 26 × 10⁻⁶. -6 / K, the top cover is made of stainless steel with a coefficient of thermal expansion of 14×10. -6 / K. α is 30°, β is 60°.

[0078] During the assembly process: Phosphate adhesive is applied to the contact surfaces of the outer shell and the top cover using a slot extrusion method at a linear velocity of 0.8 m / s. After assembly at a temperature of (15±2)℃ and a pressure of 20MPa, the pressure is released at a rate not exceeding 0.4MPa / s. Vacuum drying is carried out at a temperature of 45℃ and a pressure not exceeding 10Pa.

[0079] Example 4 This embodiment provides a method for preparing a single battery cell, which differs from Embodiment 1 in that... The casing includes an outer shell and a top cover. The outer shell is made of magnesium alloy with a coefficient of thermal expansion of 26 × 10⁻⁶. -6 / K, the top cover is made of titanium alloy Ti-3Al-2.5V, α is 30°, β is 55°.

[0080] During the assembly process: A sodium silicate-containing gel was coated on the contact surface between the outer shell and the top cover using a slit extrusion method at a linear velocity of 0.8 m / s. After assembly at a temperature of (15±2)℃ and a pressure of 20MPa, the pressure is released at a rate not exceeding 0.4MPa / s. Vacuum drying is carried out at a temperature of 45℃ and a pressure not exceeding 10Pa.

[0081] Example 5 This embodiment provides a method for preparing a single battery cell, which differs from Embodiment 1 in that... The housing consists of an outer shell and a top cover. The outer shell is made of titanium alloy Ti-3Al-2.5V, and the top cover is made of aluminum alloy AA3003. α is 30°, and β is 55°.

[0082] During the assembly process: A sol containing nano-silica particles (i.e., nano-silica particles replacing sodium silicate in Example 1) was coated on the contact surface between the outer shell and the top cover using a slit extrusion method at a linear velocity of 0.8 m / s. After assembly at a temperature of (15±2)℃ and a pressure of 20MPa, the pressure is released at a rate not exceeding 0.4MPa / s. Vacuum drying is carried out at a temperature of 45℃ and a pressure not exceeding 10Pa.

[0083] Comparative Example 1 The only difference between this comparative example and Example 1 is that, in the top cover, α is 15°.

[0084] Comparative Example 2 The only difference between this comparative example and Example 1 is that, in the top cover, α is 45°.

[0085] Comparative Example 3 The only difference between this comparative example and Example 1 is that, in the outer shell, β is 45°.

[0086] Comparative Example 4 The only difference between this comparative example and Example 1 is that, in the outer shell, β is 75°.

[0087] Comparative Example 5 The only difference between this comparative example and Example 1 is that the outer shell is made of aluminum-magnesium alloy 5052, with a coefficient of thermal expansion of 23.8 × 10⁻⁶. -6 / K, the top cover is made of aluminum alloy AA3003, with a coefficient of thermal expansion of 23.6×10. -6 / K.

[0088] Comparative Example 6 The only difference between this comparative example and Example 1 is that no sealing layer is provided during the assembly process.

[0089] The sealing performance, cycle life, and corrosion resistance of the battery cells obtained in each embodiment and comparative example are shown in Table 1. Wherein: Example 1 (α=30°, β=55°, thermal expansion coefficient difference ΔCTE=15.0×10) -6 / K) The flange angle of 30° and the groove angle of 55° form a 25° difference, which is within a suitable range. With this angle combination, the axial resistance is moderate during low-temperature assembly, and the sealant spreads evenly without being scratched; during high-temperature self-tightening, the radial component force is sufficient to generate effective wedging without being excessive, thus preventing plastic deformation. ΔCTE is 15×10⁻⁶. -6 / K provides sufficient thermal displacement to drive self-locking. The three work together to achieve optimal overall performance.

[0090] Example 2 (α=25°, β=55°, ΔCTE=9.0×10) -6 / K) Angle difference of 30° is at the upper limit, the interlocking effect is slightly stronger but ΔCTE is relatively small (9.0×10). -6 / K), but the risk of adhesive layer damage increases slightly.

[0091] Example 3 (Mg alloy / SUS304, ΔCTE=12.0×10) -6 / K) Magnesium alloy (26×10) -6 / K) and stainless steel (14×10 -6 The combination / K) has a ΔCTE of 12.0 × 10⁻⁶. -6 / K, within the effective range but with high activity. β-α increased from 25° to 30°, resulting in a slightly longer self-locking stroke but slightly increased filling difficulty. Phosphate adhesive was used, which has a slightly weaker chemical affinity to magnesium alloy surfaces than silicate systems for aluminum / titanium. The sealing layer showed very slight corrosion (thickness reduction of 0.5%) under high-temperature electrolyte immersion, but other properties were good.

[0092] Example 4 (ΔCTE=17.4×10) -6 / K) The ΔCTE of the Mg / Ti combination is as high as 17.4 × 10⁻⁶. -6 / K is the largest in all embodiments, indicating the strongest thermally induced self-driving force. β-α=25° remains the optimal range. Due to the large ΔCTE, sufficient radial force can be generated even at slightly smaller angles. Overall performance is excellent.

[0093] Example 5 (Ti / Al, flange on the outer shell, ΔCTE=15.0×10) -6 / K) By swapping the materials with those in Example 1 (the outer shell is Ti and the top cover is Al), the ΔCTE remains the same, but the direction of thermal expansion is reversed. The titanium alloy outer shell expands less, while the aluminum alloy top cover expands more. At high temperatures, the top cover tends to expand outward relative to the outer shell, exhibiting symmetrical and equivalent mechanical behavior. Using nano-SiO2 particles (i.e., replacing sodium silicate in Example 1 with SiO2 particles), the particle filling effect is slightly better than that of pure gel, and the interfacial contact resistance is the lowest (3.0%).

[0094] Comparative Example 1 (α=15°, β-α=40°) – Angle α is too small An angle of α=15° is too sharp. Physically, an excessively small α angle causes the flange to form a sharp wedge shape. This sharp wedge structure creates a stress concentration effect similar to a "knife," directly leading to two consequences: First, it scratches the coated sealant layer, causing initial, irreversible physical defects. Second, due to the low radial force conversion efficiency of sin15°, the system is forced to apply a larger axial load to achieve the same radial clamping force. This excessive axial load generates local pressure at the sharp corner that far exceeds the yield strength of the aluminum alloy shell, triggering localized plastic deformation at the shell opening. This deformation permanently widens the sealing gap, making it impossible to establish an effective "wedge self-locking" mechanism to compensate for the gap, even at high temperatures, ultimately leading to seal failure.

[0095] Comparative Example 2 (α=45°, β-α=10°) – Angle α is too large With an angle of α=45°, the slope is too gentle. While this is beneficial for assembly (sin45° has high radial conversion efficiency but low axial resistance), its geometry results in insufficient radial displacement compensation at high temperatures. When the two materials experience relative displacement due to thermal expansion differences, the gentle slope (tan45°=1) converts most of the relative motion into axial sliding rather than radial compression. In 1000 cycles of thermal shock, this design flaw prevents the effective counteracting of fretting at the interface caused by repeated material expansion and contraction. This fretting wear disrupts the chemical bond between the sealing layer and the metal substrate, leading to a sharp increase in contact resistance. Simultaneously, insufficient radial compression prevents the sealing layer from being continuously compressed to maintain airtightness.

[0096] Comparative Example 3 (β=45°, β-α=15°) – Angle β is too small The β=45° groove is too shallow, and the flange does not slide far enough along the inclined surface at high temperatures, failing to form an effective wedge-shaped self-locking effect. The interface contact pressure is only 60% of that in Example 1. The sealing path is shortened, the leakage channel increases, and the pressure drop is the largest (2.1% / h) during the pressure holding test.

[0097] Comparative Example 4 (β=75°, β-α=45°) – Angle β is too large An angle of β=75° is too large, resulting in extremely high residual compressive stress (exceeding 70% of the yield strength) at the sharp corner of the groove under 30MPa high-pressure assembly. Stress corrosion cracking occurs in the hot electrolyte environment, the sharp β angle hinders the uniform spread of the sealant, dead corners exist at the bottom of the groove, and capillary action accelerates chemical degradation (reducing the layer thickness by 15%).

[0098] Comparative Example 5 (ΔCTE=0.2×10) -6 / K) - Insufficient thermal expansion difference ΔCTE is only 0.2 × 10 -6At high temperatures, the outer shell and top cover expand almost synchronously, failing to generate effective relative displacement to drive the flange into the groove. The dynamic self-locking mechanism is completely absent, and the seal relies solely on chemical adhesion. Repeated thermal stress at the interface during thermal cycling cannot be automatically compensated, leading to a sharp increase in contact resistance (15.3%) and the worst sealing performance.

[0099] Comparative Example 6 (without sealing layer) The lack of a continuous dense barrier leads to leakage of microscopic channels at the interface.

[0100] Table 1

[0101] The test methods for sealing performance, cycle life, and corrosion resistance in Table 1 are as follows: Sealing performance: The battery is filled with 1.5 MPa nitrogen and held at that pressure for 24 hours. The pressure drop is then monitored. "No leakage" is defined as a pressure drop of <0.015% / h.

[0102] Cycle life: After 1000 high and low temperature shock cycles at -20℃ to 80℃, the increase in interfacial contact resistance between the housing and the top cover is measured.

[0103] Corrosion resistance: The assembled housing components (including the sealing layer) were immersed in 1M LiPF6 / EC-DMC electrolyte and stored at 60°C for 6 months. The percentage reduction in the thickness of the sealing layer was measured.

[0104] Those skilled in the art will understand that the above embodiments are specific examples of implementing this application, and in practical applications, various changes in form and detail can be made without departing from the spirit and scope of this application. Any person skilled in the art can make various alterations and modifications without departing from the spirit and scope of this application; therefore, the scope of protection of this application should be determined by the scope defined in the claims.

Claims

1. A battery cell, characterized in that, include: A battery cell assembly, the battery cell assembly comprising a negative electrode, a separator and a positive electrode stacked together; The housing, in which the battery cell assembly is located; Electrolyte, wherein the electrolyte is located within the housing; The housing includes an outer shell and a top cover. The material of the outer shell has a first coefficient of thermal expansion, and the material of the top cover has a second coefficient of thermal expansion. The first coefficient of thermal expansion is different from the second coefficient of thermal expansion. A sealing layer is provided between the outer shell and the top cover.

2. The battery cell according to claim 1, characterized in that, The absolute value of the difference between the first coefficient of thermal expansion and the second coefficient of thermal expansion is not less than 10 × 10⁻⁶. -6 / K.

3. The battery cell according to claim 1 or 2, characterized in that, The outer casing is made of at least one of aluminum alloy and magnesium alloy, and the top cover is made of at least one of titanium alloy and stainless steel; or, the outer casing is made of at least one of titanium alloy and stainless steel, and the top cover is made of at least one of aluminum alloy and magnesium alloy.

4. The battery cell according to claim 1, characterized in that, The outer casing has an opening, and the edge of the top cover has a first flange, and the inner side of the opening has a first groove that mates with the first flange; or, the edge of the top cover has a second groove, and the inner side of the opening has a second flange that mates with the second groove.

5. The battery cell according to claim 4, characterized in that, The top cover has a first flange at its edge, and the inside of the opening has a first groove that mates with the first flange; there is a gap between the first flange and the first groove.

6. The battery cell according to claim 4 or 5, characterized in that, Both the first flange and the second flange have a first surface and a second surface, with an angle α between the first surface and the second surface. Both the inner side of the first groove and the inner side of the second groove have a third surface and a fourth surface, with an angle β between the third surface and the fourth surface, where 20°≤β-α≤30°.

7. The battery cell according to claim 6, characterized in that, 20°≤α≤40°; and / or, 50°≤β≤70°.

8. A method for preparing a battery cell as described in any one of claims 1 to 7, characterized in that, include: A battery cell assembly and an electrolyte are obtained, wherein the battery cell assembly includes a negative electrode, a separator, and a positive electrode stacked together; Obtain the outer casing and top cover, install the battery cell assembly into the outer casing, and assemble the top cover and the outer casing into a housing; The electrolyte is injected into the housing; Perform the formation step; The housing includes an outer shell and a top cover. The material of the outer shell has a first coefficient of thermal expansion, and the material of the top cover has a second coefficient of thermal expansion. The first coefficient of thermal expansion is different from the second coefficient of thermal expansion. A sealing layer is provided between the outer shell and the top cover.

9. The method for preparing a battery cell according to claim 8, characterized in that, The assembly steps include: Sealant is applied to the contact surfaces of the outer casing and the top cover; After assembly at the first temperature and first pressure, the pressure is released at a rate not exceeding 0.5 MPa / s; Vacuum drying was performed at a second temperature and a second pressure. The first temperature is lower than the second temperature, and the first pressure is greater than the second pressure.

10. The method for preparing a battery cell according to claim 9, characterized in that, The sealant is applied by slit extrusion, with a controlled linear velocity of 0.5 m / s to 1.2 m / s.

11. The method for preparing a battery cell according to claim 10, characterized in that, The first temperature is 10℃~20℃, and the second temperature is 40℃~50℃.

12. The method for preparing a battery cell according to claim 10, characterized in that, The first pressure is 15MPa~25MPa, and the second pressure does not exceed 10Pa.

13. The method for preparing a battery cell according to claim 9 or 10, characterized in that, The sealant includes at least one of the following: a gel containing sodium silicate, a gel containing potassium silicate, a sol containing nano-silica particles, and a phosphate adhesive.

14. A battery device, characterized in that, The battery device includes a battery cell as described in any one of claims 1 to 7, or a battery cell obtained by the preparation method as described in any one of claims 8 to 13, and the battery device includes one or more of a battery module, a battery pack, and an energy storage battery.

15. An electrical appliance, characterized in that, The electrical device includes the battery device as described in claim 14, the battery device being used to provide electrical energy.

16. An energy storage device, characterized in that, The energy storage device includes the battery device as described in claim 14, the battery device being used to store electrical energy.